Find the general solution of y'' - 3y' + 2y = 2e^x

First we need to find the complementary function - the solutions of y'' -3y' + 2y = 0. By setting y=Ae^(kx) (A is a constant) we get :A(k^2 - 3k + 2)y = 0. This means k^2 - 3k + 2 = 0 =(k-1)(k-2). If 2 things multiply to give zero then at least one of them must be zero so we can have k=1 or k=2. Therefore any solution of the form y = Ae^x + Be^(2x) where A and B are constants solves y'' -3y' + 2y = 0 .
Now we need the particular integral. Since the right hand side of y'' - 3y' + 2y = 2e^x has an e^x term we guess a solution of the form y=Ce^x ( C constant). However, from above we see that this is part of the complementary function and so will not work as the left hand side of the equation will be 0. So we guess y = Cxe^x . Substituting this in we get: (Cx+2C)e^x - 3(Cx + C)e^x +2Cxe^x = 2e^xThe coefficients of xe^x cancel out to zero so we get: -Ce^x = 2e^x Which means C = -2 and therefore out general solution is: y = Ae^x + Be^(2x) - 2xe^x

Related Further Mathematics A Level answers

All answers ▸

A complex number z has argument θ and modulus 1. Show that (z^n)-(z^-n)=2iSin(nθ).


Prove that 1+4+9+...+n^2 = n(n+1)(2n+1)/6.


Take quadratic equation x^2-6x+14=0 and its solutions a and b. What is a/b+b/a?


A spring with a spring constant k is connected to the ceiling. First a weight of mass m is connected to the spring. Deduce the new equilibrium position of the spring, find its equation of motion and hence deduce its frequency f.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences